Removal of chlorophyll and pheophorbide from Chlorella pyrenoidosa by supercritical fluid extraction: potential of protein resource. Issue 7 (24th May 2021) - Miyazawa, Taiki; Higuchi, Ohki; Sasaki, Masato; Ota, Masaki; Aida, Tsutomu; Takekoshi, Hideo; Inomata, Hiroshi; Miyazawa, Teruo
ABSTRACT: This study tried to quantitatively clarify the usefulness of supercritical fluid extraction for removal of chlorophyll and pheophorbide from Chlorella pyrenoidosa. C. pyrenoidosa powder was subjected to supercritical fluid extraction, and chlorophyll a and pheophorbide a in its extracted fractions were measured by HPLC-UV. Chlorophyll a and pheophorbide a in residue after supercritical fluid extraction became below of detection limit.